2011
DOI: 10.1063/1.3575198
|View full text |Cite
|
Sign up to set email alerts
|

Copper impurities in bulk ZnO: A hybrid density functional study

Abstract: Transition metal doping of ZnO is considered as a promising way to obtain a diluted magnetic semiconducting oxide. In this work we investigate copper doping of ZnO by means of density functional theory, using a hybrid exchange-correlation functional and a periodic approach with localized atomic basis functions. Isolated copper species, such as copper substitutional to zinc, Cu s , and Cu interstitial, Cu i , are analyzed in terms of transition energy levels and hyperfine coupling constants with reference to av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
(86 reference statements)
8
16
1
Order By: Relevance
“…This feature is consistent with previous calculations concerning hydrogen adsorption 49 and Cu doping in bulk ZnO. 50 The fact that the CBM for site b coincides with the CBMs for the other systems in Fig. 2 is thus merely coincidental.…”
Section: Electronic Properties Of the Adsorbed Cu Atomsupporting
confidence: 92%
“…This feature is consistent with previous calculations concerning hydrogen adsorption 49 and Cu doping in bulk ZnO. 50 The fact that the CBM for site b coincides with the CBMs for the other systems in Fig. 2 is thus merely coincidental.…”
Section: Electronic Properties Of the Adsorbed Cu Atomsupporting
confidence: 92%
“…An acceptor level in the upper portion of the band gap may act as an electron trap but cannot produce p-type conductivity. More recent calculations that utilized hybrid density functional theory (DFT) 32 showed an acceptor level 2.7 eV above the VB, qualitatively consistent with the experimental data.…”
Section: A Coppersupporting
confidence: 72%
“…The HREELS results were further corroborated by DFT calculations [76,216]. It was found that the shallow donor states result from the interstitial Cu þ species (see Fig.…”
Section: Cu/znosupporting
confidence: 65%